PERANCANGAN APLIKASI PENGOLAHAN DATA (E-ARSIP) DOKUMEN BERITA ACARA PENGIRIMAN BARANG BERBASIS WEB - Khusnul Khoiriyah; Jamah Sari; Adam Triaji (Institut Teknologi dan Bisnis (ITB) Swadharma, 2022)
PT. Daya Eka Samudera is a company engaged in Marine Cargo Expedition (EMKL) since 2012. Most of the data processing in this company has not been computerized, such as processing of receipt data, and news of goods receipt. So, it has several problems such as difficulty in finding the Minutes of Receipt of the desired goods because they have to look for one by one, invalid data between physical and expedition books. It is quite vulnerable to manipulation, and data may be lost due to scattered or damaged expedition books. The analysis that has been carried out, using the PIECES method on the running system, found various shortcomings that require an E-Archive data processing application. The purpose of this research is to design a Web-based E-Archive application. The results have been achieved by creating an application for data processing systems e-archive documents for delivery of goods. works well, as designed